Ultrasonic-assisted encapsulation of lemongrass essential oil in HP-β-CD: Optimization, characterization, and application for mango preservation - Yuexin Pan; Wenhao Zhang; Wanzhou Yang; Zhiyuan Tai; Xia Liu; Jia Ran; Xiaodong Yu; Qiyi He (Ultrasonics Sonochemistry)
Mangoes are highly susceptible to post-harvest spoilage, leading to significant losses. This study aimed to optimize the encapsulation of lemongrass essential oil (LEO) using ultrasonic-assisted hydroxypropyl-β-cyclodextrin (HP-β-CD) and response surface methodology (RSM). The ultrasonic-assisted inclusion complex (UIC) was characterized through various techniques including particle size analysis, SEM, UV–vis, FTIR, XRD, and TGA. The antibacterial activity of the UIC was evaluated, and its effectiveness in prolonging mango shelf life was assessed by monitoring parameters such as weight loss, firmness, total soluble solids (TSS), titratable acidity (TA), malondialdehyde (MDA), vitamin C (VC) content, and external appearance. The results indicated that ultrasonic-assisted encapsulation significantly improved the encapsulation efficiency (EE), with optimal conditions of a core-wall ratio of 9:1, ultrasonic power of 150 W, and temperature of 36 °C. The UIC exhibited sustained release of LEO and enhanced antimicrobial activity, resulting in significant reductions in weight loss, firmness degradation, and metabolic changes during mango storage. Treated mangoes also showed improved appearance, with delayed onset of black spots and browning. These findings suggest that ultrasonic-assisted HP-β-CD encapsulation of LEO is an effective, eco-friendly strategy for postharvest preservation of mangoes, offering substantial potential for extending shelf life and maintaining fruit quality.